Characterization and stability studies of a novel liposomal cyclosporin A prepared using the supercritical fluid method: comparison with the modified conventional Bangham method - Karn PR (Dove Medical Press, 2013)
Pankaj Ranjan Karn,1,3 Wonkyung Cho,1,3 Hee-Jun Park,1,3 Jeong-Sook Park,3 Sung-Joo Hwang1,21Yonsei Institute of Pharmaceutical Sciences, Yonsei University, Yeonsu-gu, Incheon, Republic of Korea; 2College of Pharmacy, Yonsei University, Yeonsu-gu, Incheon, Republic of Korea; 3College of Pharmacy, Chungnam National University, Yuseong-gu, Daejeon, Republic of KoreaAbstract: A novel method to prepare cyclosporin A encapsulated liposomes was introduced using supercritical fluid of carbon dioxide (SCF-CO2) as an antisolvent. To investigate the strength of the newly developed SCF-CO2 method compared with the modified conventional Bangham method, particle size, zeta potential, and polydispersity index (PDI) of both liposomal formulations were characterized and compared. In addition, entrapment efficiency (EE) and drug loading (DL) characteristics were analyzed by reversed-phase high-performance liquid chromatography. Significantly larger particle size and PDI were revealed from the conventional method, while EE (%) and DL (%) did not exhibit any significant differences. The SCF-CO2 liposomes were found to be relatively smaller, multilamellar, and spherical with a smoother surface as determined by transmission electron microscopy. SCF-CO2 liposomes showed no significant differences in their particle size and PDI after more than 3 months, whereas conventional liposomes exhibited significant changes in their particle size. The initial yield (%), EE (%), and DL (%) of SCF-CO2 liposomes and conventional liposomes were 90.98 ± 2.94, 92.20 ± 1.36, 20.99 ± 0.84 and 90.72 ± 2.83, 90.24 ± 1.37, 20.47 ± 0.94, respectively, which changed after 14 weeks to 86.65 ± 0.30, 87.63 ± 0.72, 18.98 ± 0.22 and 75.04 ± 8.80, 84.59 ± 5.13, 15.94 ± 2.80, respectively. Therefore, the newly developed SCF-CO2 method could be a better alternative compared with the conventional method and may provide a promising approach for large-scale production of liposomes.Keywords: supercritical carbon dioxide, liposome, chemical stability, physical stability